The Influence Of Compensation, Motivation, and Workload on Employee Performance at PT Matesu Gotty Abadi - Mandasari, Fera; Hidayati, Roziana Ainul (INNOVATION RESEARCH JOURNAL, 2025)
The background to this research is that in the last three years employee performance has decreased. This research aims to test the influence of compensation, motivation and workload on employee performance at PT Matesu Gotty Abadi. This research uses quantitative methods. The population in this study were all permanent employees at PT Matesu Gotty Abadi, totaling 65 employees, while the sampling used was using a nonprobability sampling technique, namely using Saturated Samples. The reason is that taking the entire population, the sample used is also a homogeneous sample, namely 65 permanent employee respondents. The analysis technique uses instrument testing, classical assumption testing, and hypothesis testing. For testing tools, use the Statistical Package for the Social Sciences (SPSS). The results of this research show that compensation has a positive and significant effect on performance, motivation has a positive and significant effect on performance, and workload has a positive and significant effect on performance